Chemical–biological characterization of a cruzain inhibitor reveals a second target and a mammalian off-target - Choy, Jonathan W.; Bryant, Clifford; Calvet, Claudia M.; Doyle, Patricia S.; Gunatilleke, Shamila S.; Leung, Siegfried S. F.; Ang, Kenny K. H.; Chen, Steven; Gut, Jiri; Oses-Prieto, Juan A.; Johnston, Jonathan B.; Arkin, Michelle R.; et al. (Beilstein Journal of Organic Chemistry, 2013)
Inhibition of the Trypanosoma cruzi cysteine protease cruzain has been proposed as a therapeutic approach for the treatment of Chagas’ disease. Among the best-studied cruzain inhibitors to date is the vinylsulfone K777 (1), which has proven effective in animal models of Chagas’ disease. Recent structure–activity studies aimed at addressing potential liabilities of 1 have now produced analogues such as N-[(2S)-1-[[(E,3S)-1-(benzenesulfonyl)-5-phenylpent-1-en-3-yl]amino]-3-(4-methylphenyl)-1-oxopropan-2-yl]pyridine-4-carboxamide (4), which is trypanocidal at ten-fold lower concentrations than for 1. We now find that the trypanocidal activity of 4 derives primarily from the inhibition of T. cruzi 14-α-demethylase (TcCYP51), a cytochrome P450 enzyme involved in the biosynthesis of ergosterol in the parasite. Compound 4 also inhibits mammalian CYP isoforms but is trypanocidal at concentrations below those required to significantly inhibit mammalian CYPs in vitro. A chemical-proteomics approach employing an activity-based probe derived from 1 was used to identify mammalian cathepsin B as a potentially important off-target of 1 and 4. Computational docking studies and the evaluation of truncated analogues of 4 reveal structural determinants for TcCYP51 binding, information that will be useful in further optimization of this new class of inhibitors.
Keywords: activity-based probes; Chagas’ disease; cruzain; CYP51; 14-α-demethylase; hybrid drugs; Trypanosoma cruzi